Retinopathy of prematurity and placental histopathology findings: A retrospective cohort study - Athikarisamy, Sam Ebenezer; Lam, Geoffrey C.; Cooper, Matthew N.; Strunk, Tobias (Frontiers in Pediatrics, 2023)
Aim Retinopathy of prematurity (ROP) is a biphasic vaso-proliferative disease that has the potential to cause blindness. In addition to prematurity and hyperoxia, perinatal infection and inflammation have been attributed to play a critical role in the pathogenesis of ROP. The aim of this study was to assess the association between placental inflammation and the severity of ROP. Methods A retrospective study of infants (<30 weeks of gestational age) born at the King Edward Memorial Hospital a tertiary perinatal centre in Western Australia. Results There were 878 infants (ROP stage 0-2 = 829; 3 or more = 49). The presence of maternal chorioamnionitis appears to show signs of an association with reduced odds of severe ROP: mild chorioamnionitis OR 0.43 (95% CI 0.17,1.05) and severe chorioamnionitis OR 0.68 (95% CI 0.29,1.60). A strong association was observed for oxygen supplementation at 36 weeks (OR 5.16; p <0.001), exposure to postnatal steroids (OR 6.65; p <0.001) and receipt of platelet transfusion (OR 8.21; p <0.001). Conclusion Maternal chorioamnionitis or fetal chorioamnionitis was associated with reduced odds of severe ROP. A strong association was found in infants who needed oxygen supplementation at 36 weeks and steroid and platelet requirements in the postnatal period.